2014
DOI: 10.1002/clen.201300844
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Enriched Eutrophication Promotes the Invasion of Spartina alterniflora in Coastal China

Abstract: Pollution‐driven eutrophication is a significant by‐product of rapid economic growth in China. Such environmental changes have huge consequences on local biodiversity and ecosystem functions through the spread of invasive introduced species. Spartina alterniflora has been spreading quickly and extensively throughout China since the mid 1980s, soon after its intentional introduction from the eastern United States. The range expansion of S. alterniflora coincides with a significant increase in the per unit stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…However, nutrients (N) and their interactions, S × N, S × N × C, had significant effects on the morphological traits of both species. This result agrees with our hypothesis, and several researchers have found that increasing nutrient concentrations overcomes the stress of submergence and encourages plants to grow under these conditions, especially for invasive plant species [7,23,27]. Plant heights of both the species were increasing under submergence and nutrients treatments (Table 2, Figure 4a,b).…”
Section: Morphological Traits Under Submergence and Eutrophicationsupporting
confidence: 92%
See 2 more Smart Citations
“…However, nutrients (N) and their interactions, S × N, S × N × C, had significant effects on the morphological traits of both species. This result agrees with our hypothesis, and several researchers have found that increasing nutrient concentrations overcomes the stress of submergence and encourages plants to grow under these conditions, especially for invasive plant species [7,23,27]. Plant heights of both the species were increasing under submergence and nutrients treatments (Table 2, Figure 4a,b).…”
Section: Morphological Traits Under Submergence and Eutrophicationsupporting
confidence: 92%
“…Biomasses of many plants was increased or maintained under submergence [46] (Table 1, Figure 2) because plants used the quiescence technique to tolerate submergence [26]. WC maintained a higher root-to-shoot ratio in all treatments under monoculture, which was the plants strategy to cope with submergence and eutrophication [36], while WT maintained a better stem mass ratio under all treatments in monoculture, because adventitious roots were a tolerance stratagem of WT to survive these conditions and also provided structural stability to maintain sexual reproduction [7,24]. Total biomass of both species was increased under both submergence and three nutrient levels' interaction because more than 65% of plants of both species were above the water surface due to plant height elongation [47].…”
Section: Biomass Response Under Submergence and Eutrophicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the response to nutrient enrichment is species specific, coastal eutrophication might change marsh plant community structure by altering plant competitive balance (Bertness et al 2002, Pennings et al 2005. The strong response of S. alterniflora to exogenous nutrients allows it to outcompete native plants, colonizing bare mudflats and replacing native plants rapidly (including broadly dominant P. australis and other locally dominant species, such as S. mariqueter and S. salsa) throughout the coastal salt marsh ecosystems in China (Zhao et al 2015). Consequently, the distribution of this species has increased exponentially (Davidson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…, Zhao et al. ), while in other cases nutrients facilitate coexistence between native and introduced species or disproportionately promote natives (e.g., Firn et al. ).…”
Section: Discussionmentioning
confidence: 99%